Study the Antibacterial Mechanism of Diclofenac and its Activity Alone or Combined with Ciprofloxacin in Treating Urinary Tract Infection - Frah Razzaq Kbyeh; Ahmed N. Abedsalih (Wasit Journal for Pure Sciences, 2023)
This study aimed to compare the effects of diclofenac, ciprofloxacin and their combination groups on urine tract infection (U.T.I.s) caused by resistance  E coli 0157 H7 in vitro and in vivo. Two hundred urine samples were collected from adult women patients suffering from U.T.I.s from February 2022 to July 2022. The urine specimen was cultured on the blood agar and then incubated at 37°C for (1-2) days; MacConkey agar is the media used for determining the biochemistry results, and identification by  Rapidchek test which was performed on typical colonies from the selective plate. The M.I.C effect of Diclofenac began at (25600µg/ml) against resistance E coli 0157H7 while M.I.C of ciprofloxacin it was at (0.96mg/ml), but M.I.C of a combination between (diclofenacn+ciprofloxacin) it was at (400+0.48) mg/ml. Resistance induction assay,with the ciprofloxacin has increased four times, while with  the diclofenac has doubled, whilst the combination between (diclofenacn+ciprofloxacin) has no changed after 21 days, according to M.I.C.in the time-kill assay, it was proved that the ciprofloxacin and the combination between (diclofenacn+ciprofloxacin) works after 6 hours, compared to the diclofenac, which started to reduce  bacterial counting after 40. After that, the examination was carried out by scanning electronic microscope (S.E.M.) to exam  the mechanics of diclofenac,work  which was found that it was works as anti-biofilm In this study, forty-eighth  (48) rabbits were used and divided into six groups as follow positive control (P.C.), negative control (N.C.), diclofenac (D.C.) in 1mg/kg group, ciprofloxacin (C.I.P.)in7mg/kg group, combination (ciprofloxacin 3.5 mg/kg+diclofenac1mg/kg)COM1 group and combination (ciprofloxacin 1.75 mg/kg+diclofenac1mg/kg) com2 All  animals (injected with  0.1 ml in  CFU E coli 0157 H7 by urinary catheterization route excepting negative control all group excepting negative control resulted in a significant increase in pus cell, epithelium cell concentration in the urine after three days E coli 0157 H7  infection comparison with negative control while  in all experimental period  after (14 days) showed no significant (P < 0.05) between positive control (P.C.) and diclofenac treated groups but combination  COM1 group and com2  decrease significantly (P< 0.05)  after (seven and fourteen) days comparison with positive control. diclofenac can be combined with antibiotics as an anti-virulence agent, enhancing the immune system's ability to eradicate infection